Physical model structure capillary porous media based oriented fiberfill - Колосов, Олександр Євгенович; Сівецький, Володимир Іванович; Колосова, Олена Петрівна; Кричковська, Лілія Анатоліївна (Eastern-European Journal of Enterprise Technologies, 2013)
It is shown that the prediction of the kinetics of impregnation process oriented and woven fibrous fillers epoxy binder solution is based primarily on an analysis of the structure of fibrous fillers. In this case, the capillary structure of fibrous fillers should include the most important factors that affect the speed and completeness of the impregnation process, after impregnating fluid flow in these materials is a process, which is mainly governed by laws of capillarity and viscosity. It is shown that in general the capillary structure of any fibrous material consists of material microstructure fiber from which it is made, as well as macro-fiber material, the diameter of the capillaries of the two structures is a completely different order. Are analyzed that the penetration depth of the liquid in the impregnation of capillaries in individual fibers, especially for those short periods during which there is a treatment, there can be significant. Therefore infinitely more practical importance is the penetration of impregnating fluid in the space between the fibers (interfiber space or penetration) or filaments of fibrous material. Describes an effective approach to the selection of an adequate physical model of capillary-porous bodies in the technology of construction of the oriented fiber composites. This physical model is then used for the determination of refined mathematical model of the process of impregnation of fibrous fillers epoxy bonding using conventional filtration theory of laminar flow of viscous non-Newtonian fluid which is not compressed.